Learning Strategies in Grammar Class by EFL Successful Students at a Pesantren-Based University - Nuraini, Eka Indah; Dipta, Dinar; Virgiyanti, Diska Fatima; Fachriza, Aries; Aniesa, Aniesa (Universitas PGRI Madiun, 2023)
Along with the widespread discussion about student-centered learning, learning strategies are believed to be tools in helping students master their target language and grasp information properly. However, most students have no idea dealing with the learning strategies they have implemented. Therefore, this study aimed at discovering the practice of learning strategies in English grammar class by five successful students of the English Department at a Pesantren-based university. A qualitative case study was utilized in this investigation. The data were acquired from five successful students in their first years in learning English Grammar by collecting questionnaires and conducting in-depth interviews. In analyzing the data, the researchers used four techniques, namely data reduction, data display, generating conclusions, and verification. From the findings, successful students practiced almost all Oxford’s strategies. It meant that successful students practiced various strategies to catch up with their learning goals. In addition, the most commonly adopted strategy by the successful students was metacognitive.